The Fuchs corneal dystrophy-associated CTG repeat expansion in the TCF4 gene affects transcription from its alternative promoters - Sirp, Alex; Leite, Kristian; Tuvikene, Jürgen; Nurm, Kaja; Sepp, Mari; Timmusk, Tõnis (Scientific reports, 2020)
The CTG trinucleotide repeat (TNR) expansion in Transcription factor 4 (TCF4) intron 3 is the main cause of Fuchs’ endothelial corneal dystrophy (FECD) and may confer an increased risk of developing bipolar disorder (BD). Usage of alternative 5′ exons for transcribing the human TCF4 gene results in numerous TCF4 transcripts which encode for at least 18 N-terminally different protein isoforms that vary in their function and transactivation capability. Here we studied the TCF4 region containing the CTG TNR and characterized the transcription initiation sites of the nearby downstream 5′ exons 4a, 4b and 4c. We demonstrate that these exons are linked to alternative promoters and show that the CTG TNR expansion decreases the activity of the nearby downstream TCF4 promoters in primary cultured neurons. We confirm this finding using two RNA sequencing (RNA-seq) datasets of corneal endothelium from FECD patients with expanded CTG TNR in the TCF4 gene. Furthermore, we report an increase in the expression of various other TCF4 transcripts in FECD, possibly indicating a compensatory mechanism. We conclude that the CTG TNR affects TCF4 expression in a transcript-specific manner both in neurons and in the cornea.
Gesehen am 10.06.2021